The Effect of Split Share Reform on Earning Management in China - LI, CHEN (2017)
This research investigates the effects of split share reform on earnings management in China. Both tradable shareholders and non-tradable shareholders have the right to vote for the person who will be the board of director, and they can vote to determine the company’s policy, including such as decisions as whether to issue securities, or whether corporate action needs to change. They also have the right to distribute the cash flow of the company. The split share structure creates a conflict of interest between tradable and non-tradable shareholders. To address this the Chinese Securities Regulatory Commission (CSRC) initiated the split share reform to convert non-tradable shares into tradable shares in April 2005. This research confirms that after the split share reform, the increase in number of tradable shareholdings has had a positive effect on earnings management, while non-tradable shareholdings have been negatively affected by earnings management. The research will also study the relationship between split share reform and executive compensation, which will then relate to earnings management, in accordance with earlier studies.